Gain Scheduling LQR Control of Linear Parameter Varying Overhead Crane - Aktas, Ayhan; Sever, Mert; Yazici, Hakan (IEEE, 2016)
In this study, an overhead crane having time varying parameters, represented by a Linear Parameter Varying (LPV) state space system. In order to achieve position tracking with minimum sway angle, Gain Scheduling (GS) control approach has been used. Therefore, time varying parameters such as load mass and rope length are treated as Scheduling Parameters (SP). Then, LPV LQR controller is designed with the use of Linear Matrix Inequalities (LMIs). Effectiveness of the proposed controller investigated by numerical simulation studies. Simulations indicate that proposed controller has superior performance, since the response of nominal controller adversely effected by parameter variations.
Keywords: Engineering